2017
DOI: 10.1021/acsami.6b15804
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt Oxide Nanoclusters on Rutile Titania as Bifunctional Units for Water Oxidation Catalysis and Visible Light Absorption: Understanding the Structure–Activity Relationship

Abstract: The structure of cobalt oxide (CoO) nanoparticles dispersed on rutile TiO (R-TiO) was characterized by X-ray diffraction, UV-vis-NIR diffuse reflectance spectroscopy, high-resolution transmission electron microscopy, X-ray absorption fine-structure spectroscopy, and X-ray photoelectron spectroscopy. The CoO nanoparticles were loaded onto R-TiO by an impregnation method from an aqueous solution containing Co(NO)·6HO followed by heating in air. Modification of the R-TiO with 2.0 wt % Co followed by heating at 42… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
50
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 35 publications
5
50
0
Order By: Relevance
“…[98] Modification of rutile TiO 2 with 2.0 wt %c obalt followedb yh eating at 423 Kf or 1hresulted in the highest photocatalytic activity,w hichw as higher than an analogousm aterialo ptimally modified with Co(OH) 2 .P hysicochemicala nalyses indicated that the activity of this photocatalyst was dependent on the formation of Co 3 O 4 nanoclusters with an optimal distribution. [98] Modification of rutile TiO 2 with 2.0 wt %c obalt followedb yh eating at 423 Kf or 1hresulted in the highest photocatalytic activity,w hichw as higher than an analogousm aterialo ptimally modified with Co(OH) 2 .P hysicochemicala nalyses indicated that the activity of this photocatalyst was dependent on the formation of Co 3 O 4 nanoclusters with an optimal distribution.…”
Section: Sensitization By Cobalttowardw Ater Oxidation Under the Entimentioning
confidence: 95%
See 2 more Smart Citations
“…[98] Modification of rutile TiO 2 with 2.0 wt %c obalt followedb yh eating at 423 Kf or 1hresulted in the highest photocatalytic activity,w hichw as higher than an analogousm aterialo ptimally modified with Co(OH) 2 .P hysicochemicala nalyses indicated that the activity of this photocatalyst was dependent on the formation of Co 3 O 4 nanoclusters with an optimal distribution. [98] Modification of rutile TiO 2 with 2.0 wt %c obalt followedb yh eating at 423 Kf or 1hresulted in the highest photocatalytic activity,w hichw as higher than an analogousm aterialo ptimally modified with Co(OH) 2 .P hysicochemicala nalyses indicated that the activity of this photocatalyst was dependent on the formation of Co 3 O 4 nanoclusters with an optimal distribution.…”
Section: Sensitization By Cobalttowardw Ater Oxidation Under the Entimentioning
confidence: 95%
“…Then, the structure of cobalt oxide nanoparticles, which were loaded on the rutile TiO 2 surfaceb ya ni mpregnation methodf rom an aqueous solution containing Co(NO 3 ) 2 ·6 H 2 O followed by heatingi na ir,w as systematically studied by meanso fX-ray diffraction, UV/Vis/NIR diffuse reflectance spectroscopy,h igh-resolution transmission electron microscopy,Xray absorption fine-structures pectroscopy,a nd X-ray photoelectrons pectroscopy. [98] Modification of rutile TiO 2 with 2.0 wt %c obalt followedb yh eating at 423 Kf or 1hresulted in the highest photocatalytic activity,w hichw as higher than an analogousm aterialo ptimally modified with Co(OH) 2 .P hysicochemicala nalyses indicated that the activity of this photocatalyst was dependent on the formation of Co 3 O 4 nanoclusters with an optimal distribution. These nanoclustersa re considered to interactw ith the TiO 2 surface, which leads to visible light absorption and activesites for water oxidation.…”
Section: Sensitization By Cobalttowardw Ater Oxidation Under the Entimentioning
confidence: 95%
See 1 more Smart Citation
“…It is well-known that TiO 2 has three different crystal phases, anatase, brookite and rutile [15]. Notably, the rutile TiO 2 has attracted great research interest due to the fact that it is the most stable phase in thermodynamics, compared to the other two crystalline phases [16][17][18]. Rutile TiO 2 is suitable for photocatalytic water splitting due to its appropriate band energy position.…”
Section: Introductionmentioning
confidence: 99%
“…Oxides of iridium or ruthenium are known to be effective in water oxidations, 41 however more recently cobalt oxide has been found to be an effective low cost catalyst. 43,44,45,46,47 In addition, MnOx species has been reported to enhance the water oxidation ability of cobalt oxide. 48,49,50 We therefore investigated first the effect of particle size of cobalt oxide and further the presence of Mn on water oxidation ability of Co3O4.…”
Section: Water Oxidation Activity Of Cobalt Oxide and Manganese Modifmentioning
confidence: 99%